2020
DOI: 10.3390/vetsci7030115
|View full text |Cite
|
Sign up to set email alerts
|

Training of Primary Chicken Monocytes Results in Enhanced Pro-Inflammatory Responses

Abstract: Beta-glucan-stimulated mammalian myeloid cells, such as macrophages, show an increased responsiveness to secondary stimulation in a nonspecific manner. This phenomenon is known as trained innate immunity and is important to prevent reinfections. Trained innate immunity seems to be an evolutionary conserved phenomenon among plants, invertebrates and mammalian species. Our study aimed to explore the training of primary chicken monocytes. We hypothesized that primary chicken monocytes, similar to their mammalian … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(74 reference statements)
1
8
0
1
Order By: Relevance
“…Re-challenge with C. perfringens (MOI = 5) resulted in a significantly higher release of extracellular DNA in HK- C. albicans -primed PBMC ( Figure 4(b) ), thereby it showed increased the ability to kill bacteria of PBMC ( Figure 4(c) ). Consistent with previous reports about trained immunity in chicken [ 28 ], we observed an increased production of antimicrobial NO upon stimulation with C. perfringens (MOI = 10) is stronger in HK- C. albicans -primed PBMCs compared to non-primed PBMCs ( Figure 4(d) ). Unstimulated cells were used as controls for the basal level.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Re-challenge with C. perfringens (MOI = 5) resulted in a significantly higher release of extracellular DNA in HK- C. albicans -primed PBMC ( Figure 4(b) ), thereby it showed increased the ability to kill bacteria of PBMC ( Figure 4(c) ). Consistent with previous reports about trained immunity in chicken [ 28 ], we observed an increased production of antimicrobial NO upon stimulation with C. perfringens (MOI = 10) is stronger in HK- C. albicans -primed PBMCs compared to non-primed PBMCs ( Figure 4(d) ). Unstimulated cells were used as controls for the basal level.…”
Section: Resultssupporting
confidence: 92%
“…Trained immunity is an evolutionarily conservative innate immune mechanism that exists in multiple vertebrate species including mammals [ 26 ], chickens [ 28 ], and fishes [ 42 ]. This study showed that exposure to C. perfringens increases the production of NO in primed PBMC compared to non-primed.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, β-glucan improved the action of an inactivated rabies vaccine by stimulation of both B and T lymphocytes [ 103 ]. β-Glucan was also found to induce significant trained immunity in chicken monocytes, similarly to mammals [ 104 ]. So far, no epigenetic changes have been found, but this is probably due to the limited number of studies using avian models.…”
Section: β-Glucanmentioning
confidence: 99%
“…β-Glucan was reported to increase phagocytosis, bactericidal activity, and oxidative burst in chicks ( Lowry et al, 2005 ). β-Glucan treatment could also induce trained innate immunity in primary chicken monocytes ( Verwoolde et al, 2020 ). A study in humans also suggested that β-glucan induces trained immunity by enriching histone modification at the promoter regions of proinflammatory genes in human monocytes ( Domínguez-Andrés et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%